Evaluation of Google search trends for liver diseases in Europe - Teufel, Andreas; Itzel, Timo; Zimmermann, Anca; Dumitrascu, Dan; Bugianesi, Elisabetta; Valenti, Luca; Castera, Laurent; Carrieri, Patrizia; Crespo, Javier; Romero-Gomez, Manuel; Flisiak, Robert; Krawczyk, Marcin; et al. (Journal of gastrointestinal and liver diseases, 2024)
Background and Aims: Chronic liver diseases belong to the most common diseases worldwide and are associated with increased morbidity and mortality. Although more than one in three adults are estimated to have metabolic dysfunction-associated steatotic liver disease (MASLD), awareness of this condition is low amongst the general public, health care professionals and policy makers. However, meaningful knowledge transfer is essential for raising awareness and improving prevention and treatment. This study set out to investigate the use of the major internet search engine to understand how knowledge transfer has evolved by analyzing liver-related searches trends. - Methods: We investigated Google search trends by measuring the number of hits relating to liver diseases between 2004 and 2021 in seven languages and European countries but also worldwide. All analyses were performed in R using the R Google trends package gtrendsR. - Results: We found that interest in MASLD [formerly non-alcoholic fatty liver disease (NAFLD)] has generally increased over time, but that interest in metabolic associated steatohepatitis (MASH) - the most severe form of MASLD - has decreased. Interest in viral hepatitis C has decreased, whereas the number of queries regarding viral hepatitis B have been stable but dominated by interest in vaccination for it. Recent medical developments (in viral hepatitis) did not lead to a noticeable change in overall search behavior. Users preferred searching using their native language and less complex medical terms and acronyms (e.g., fatty liver instead of NAFLD). - Conclusions: In the last two decades, Google search trends have followed the general development in the field of hepatology. Searches were dominated by non-experts and are not being rapidly influenced by novel scientific developments. Also, users preferred search terms in their native languages rather than English and tended to avoid complex medical search terms. Awareness and communication strategies around MASLD should consider these preferences when addressing the general public.